2019
DOI: 10.3892/ol.2019.11158
|View full text |Cite
|
Sign up to set email alerts
|

DNA demethylation agent 5azadC downregulates HPV16 E6 expression in cervical cancer cell lines independently of TBX2 expression

Abstract: HPV16 is the most carcinogenic human papillomavirus and causes >50% of cervical cancers, the majority of anal cancers and 30% of oropharyngeal squamous cell carcinomas. HPV carcinogenesis relies on the continuous expression of the two main viral oncoproteins E6 and E7 that target >150 cellular proteins. Among them, epigenetic modifiers, including DNA Methyl Transferases (DNMT), are dysregulated, promoting an aberrant methylation pattern in HPV-positive cancer cells. It has been previously reported that the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…CIN lesions are subdivided into low, medium and high risk. Gray dotted guidelines for z-score of [-2, -1, 1, 2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIN lesions are subdivided into low, medium and high risk. Gray dotted guidelines for z-score of [-2, -1, 1, 2].…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation plays a crucial role in gene regulation and occurs mainly at CG dinucleotide sequences in mammalian genomes [1]. In HPV-induced cancers of the cervix and vulva HPV infection is the key driver of DNA methylation changes as the HPV genes E6 and E7 affect the activity of DNA methyltransferases [2]. For HPV-independent cancers DNA methylation changes are often induced by mutations in genes involved in epigenetic processes such as DNA methyltransferases [3].…”
Section: Introductionmentioning
confidence: 99%
“…In a case report, azacitidine was used to treat a 57-year-old woman newly diagnosed with MDS during palliative chemotherapy for metastatic breast cancer, azacitidine showed promising effects for MDS, and also stabilized the patient’s lung and lymph node metastases without any major toxicity ( Baek et al, 2019 ). An increasing number of clinical trials of demethylating treatment is ongoing, some of which have presented exciting effects ( Linnekamp et al, 2017 ; Perrard et al, 2020 ; Singal et al, 2015 ; Jansen et al, 2019 ) ( Table 3 ). A Phase I study showed the security of decitabine treated by hepatic arterial infusion, and a dose level of 20 mg/m 2 /day on five consecutive days every 4 weeks could be considered for further investigation in combinatorial immunotherapy regimens in patients with Unresectable Liver-predominant Metastases From Colorectal Cancer ( Singal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a case report, azacitidine was used to treat a 57-year-old woman newly diagnosed with MDS during palliative chemotherapy for metastatic breast cancer, azacitidine showed promising effects for MDS, and also stabilized the patient's lung and lymph node metastases without any major toxicity 30 . Now, An increasing number of clinical trials of demethylating treatment is ongoing,some have presented exciting effects [31][32][33][34] (Table 2). A Phase I study showed the security of decitabine treated by hepatic arterial infusionin, and a dose level of 20 mg/m2/day on five consecutive days every 4 weeks could be considered for further investigation in combinatorial immunotherapy regimens in patients with Unresectable Liver-predominant Metastases From Colorectal Cancer 33 .…”
Section: Discussionmentioning
confidence: 99%